An impact of Cr-doping on physical properties of PbI2 thin films facilely deposited by spin coating technique. (February 2020) - Khan, Mohd Taukeer; Shkir, Mohd.; Yahia, I.S.; Almohammedi, Abdullah; AlFaify, S.
Abstract: Herein, we report the effect of Cr-doping concentrations (0.0, 1.0, 3.0, 5.0, 7.5 wt%) on the physical properties of PbI2 thin films fabricated through cost effective spin coating method. The XRD pattern reveals that the fabricated PbI2 thin films have 2H-polytype structure. The Cr-doping in PbI2 thin films were confirmed via Raman spectra and EDX/SEM mapping. The surface morphology of pure PbI2 films reveals that the spherical nanoparticles are uniformly assembled throughout the surface of PbI2 films and morphology of the film enormously change with Cr-doping. The optical study shows that the parameters such as dielectric constant, refractive and absorption indexes primary rises for Cr-content up to 1% and later start decreasing for concentrations >1%. The direct band gap of Cr-doped PbI2 thin films was found to be decreased to 2.34 eV in comparison to 2.43 eV of pure PbI2 thin films. The optical conductivity for pure PbI2 thin films was evaluated and found to be decreases with Cr-doping concentrations. Finally, nonlinear optical properties of the fabricated thin films were investigated and observed that the optical susceptibilities first increase for 1% Cr-doping concentration and systematically decreases for higher doping concentrations. Highlights: First time, nanostructured Cr:PbI2 thin films were fabricated facilely using spin coater. Structural and vibrational analyses confirm mono-phase and good crystallinity of films. Homogeneous Cr doping in PbI2 was confirmed by EDX/SEM e-mapping and low dimension nanoparticles formation. Eg values are estimated to be in range of 2.34–2.43 eV for pure and Cr:PbI2 films. The high order of χ(3) and n (2) values are found in Cr:PbI2 films.